Pengembangan Strategi Pemasaran Inovatif Untuk Memperluas Pasar Produk Citul Mantul Melalui Program Magang Wirausaha Merdeka - Dini Anggraeni (Lembaga Pengembangan Kinerja Dosen, 2024)
An entrepreneurial internship is a process of training students to become entrepreneurs so that after graduating students can open employment opportunities. So this independent entrepreneurship program is a way to test students' skills in preparing for the future and improving the skills they have from college. This internship program runs for 4 months from 8 August to 22 November. In this internship program we are taught how to start a business and what it takes to become an entrepreneur. The business that I ran while participating in this program was the food product